UPAYA MENGURANGI PERILAKU PROKRASTINASI SISWA DENGAN PENERAPAN LAYANAN INFORMASI MENGGUNAKAN MEDIA AUDIO VISUAL : UPAYA MENGURANGI PERILAKU PROKRASTINASI SISWA DENGAN PENERAPAN LAYANAN INFORMASI MENGGUNAKAN MEDIA AUDIO VISUAL - Wira Yudha, Akbir (Kopertis Region IV Jabar and Banten, 2025)
Abstract A delayed task can be caused by being preoccupied with completing other, less urgent tasks that are not prioritized. In addition, postponing assignments or tasks may also occur intentionally due to laziness, which can become a daily habit. The main factor contributing to procrastination is often a lazy attitude accompanied by the assumption that there is still plenty of time to complete the obligations or assignments that need to be done. Therefore, this study aims to overcome students' academic procrastination behavior through the implementation of informational services using audiovisual media for Grade XI students at SMAN 10 Palembang. The subjects of this study were Grade XI students at SMAN 10 Palembang. This research is a guidance action research (Penelitian Tindakan Layanan or PTL), using pre- and post-test questionnaires. The study was conducted in three cycles, with each cycle consisting of two sessions of informational services. The results of the study indicate that addressing academic procrastination through informational services using audiovisual media is highly effective. This is evidenced by the pre-test percentage in Cycle I, Session I, which was 92%, followed by a post-test percentage of 87%. In Cycle II, the percentage was 71%, and in Cycle III, the result decreased to 68%. Observation sheets for each cycle during the implementation of the services showed that in Cycle I, Session I, the observation score reached 80%, and in Session II it dropped to 75%. In Cycle II, Session I, the percentage was 74%, and in Session II it was 71%. In Cycle III, Session I, the percentage was 68%, and in Session II it remained at 68%. Keywords: Academic Procrastination, Information Services, Audio-Visual Media